IFPA meeting 2016 workshop report II: Placental imaging, placenta and development of other organs, sexual dimorphism in placental function and trophoblast cell lines. - Adibi, J; Burton, G; Clifton, V; Collins, S; Frias, A; Gierman, L; Grigsby, P; Jones, H; Lee, C; Maloyan, A; Markert, U; Morales-Prieto, D; et al. (Elsevier, 2017)
Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialized topics. At IFPA meeting 2016 there were twelve themed workshops, four of which are summarized in this report. These workshops addressed challenges, strengths and limitations of techniques and model systems for studying the placenta, as well as future directions for the following areas of placental research: 1) placental imaging; 2) sexual dimorphism; 3) placenta and development of other organs; 4) trophoblast cell lines.